Enhanced photoelectrochemical conversion performance of ZnO quantum dots sensitized α-Fe2O3 thin films. (4th May 2015) - Ikram, Ashi; Sahai, Sonal; Rai, Snigdha; Dass, Sahab; Shrivastav, Rohit; Satsangi, Vibha R.
Abstract: ZnO quantum dots (QDs) sensitized electrodeposited α-Fe2 O3 thin films have been investigated for their photoelectrochemical performance at various sensitization times. 24 h ZnO QDs sensitization in α-Fe2 O3 thin film exhibited 5.5 fold enhancement in the photocurrent density. This sample shows the highest photocurrent density of 2.84 mA cm −2 at 0.75 V/SCE electrode potential. XRD, HRTEM, EDX, FESEM, UV–visible spectroscopy and Mott–Schottky studies have also been carried out to examine the cause of the improved PEC response of sensitized samples of α-Fe2 O3 . Enhanced photocurrent exhibited by α-Fe2 O3 thin film after ZnO QDs sensitization has been mainly attributed to efficient charge separation due to the presence of ZnO QDs and to the catalytic behavior of ZnO. Highlights: Narrow band gap α-Fe2 O3 has been sensitized with wide band gap ZnO QDs. Improved PEC response of α-Fe2 O3 after ZnO QDs sensitization has been highlighted. Sensitization of ZnO QDs results in reduced recombination and also shows photocatalytic effect. Amount of ZnO QDs is crucial in deciding the PEC response.